Oxford Academic Vocabulary Practice: Lower-Intermediate B1 - Moore, J. Julie (Oxford University Press, 2021)
Oxford Academic Vocabulary Practice is for students who want to study any subject in English at university level. 250 activites help you learn and practice over 650 key words that you needto use in your written work. The vocabulary is sourced from the Oxford Corpus of Academic English - an 85-million-word corpus of academic sources. It shows how words are used across the four main subject areasof physical sciences, life sciences, social sciences and humanities.